2012
DOI: 10.1073/pnas.1211405109
|View full text |Cite
|
Sign up to set email alerts
|

Perturbation of fetal liver hematopoietic stem and progenitor cell development by trisomy 21

Abstract: The 40-fold increase in childhood megakaryocyte-erythroid and B-cell leukemia in Down syndrome implicates trisomy 21 (T21) in perturbing fetal hematopoiesis. Here, we show that compared with primary disomic controls, primary T21 fetal liver (FL) hematopoietic stem cells (HSC) and megakaryocyte-erythroid progenitors are markedly increased, whereas granulocyte-macrophage progenitors are reduced. Commensurately, HSC and megakaryocyte-erythroid progenitors show higher clonogenicity, with increased megakaryocyte, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
171
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 146 publications
(196 citation statements)
references
References 39 publications
(69 reference statements)
25
171
0
Order By: Relevance
“…While the current study focuses on the role of GATA1s mutations in erythropoiesis, our findings also provide insights into how these mutations interact with T21. Previous work has shown that T21 augments erythropoiesis in primary fetal cells (61)(62)(63) and iPSCs (18,64). Here, we confirm these findings in T21/WT GATA1 iPSCs and demonstrate that GATA1s overrides the erythropoietic effects of T21 in isogenic double-mutant T21/GATA1s iPSCs derived from 2 different patients with TMD.…”
Section: Discussionsupporting
confidence: 88%
“…While the current study focuses on the role of GATA1s mutations in erythropoiesis, our findings also provide insights into how these mutations interact with T21. Previous work has shown that T21 augments erythropoiesis in primary fetal cells (61)(62)(63) and iPSCs (18,64). Here, we confirm these findings in T21/WT GATA1 iPSCs and demonstrate that GATA1s overrides the erythropoietic effects of T21 in isogenic double-mutant T21/GATA1s iPSCs derived from 2 different patients with TMD.…”
Section: Discussionsupporting
confidence: 88%
“…Defects specific to certain aneuploidies as well as defects observed in all aneuploid strains analyzed were evident in our aneuploid HSCs. The lineage-specific defects such as reduced B-cell number observed in trisomy 16 FL-HSC reconstitutions are likely due to chromosome-specific effects, as B-cell differentiation defects have also been observed in DS (Roy et al 2012;Lane et al 2014). Furthermore, we observed decreased proliferative potential in all aneuploidy models that we examined.…”
Section: The Effects Of Aneuploidy and Cin On Hsc Fitness And Hematopmentioning
confidence: 50%
“…Various haematopoietic diseases originate prenatally (Hunger et al, 1998;Greaves, 2005;Hong et al, 2008;Roy et al, 2012;Barrett et al, 2016), and oncogenic mutations in developing haematopoietic progenitors or stem cells can lead to pre-leukaemic changes that may not be manifested if the oncogene is activated in the adult counterparts (Barrett et al, 2016). The molecular mechanisms that regulate development and maintenance of haematopoietic progenitor and stem cells in the embryo differ significantly from those in the adult, and the functional heterogeneity that appears within the emerging HSC population during development further complicates our understanding of HSC regulation (Copley et al, 2012;Crisan et al, 2015;Beaudin et al, 2016).…”
Section: Future Directions and Challengesmentioning
confidence: 99%